THE ETERNITY OF NATURE ACCORDING TO THE PHILOSOPHER IN IMAM AL-GHAZALI'S TAHAFUT AL-FALASIFAH - Melani Melani; Endang Ekowati (Program Pascasarjana UIN Sumatera Utara, 2026)
This study examines the concept of the eternity of the world (qidam al-‘ālam) in the perspective of Muslim philosophers and its critique in Tahafut al-Falasifah by Imam al-Ghazali. The research aims to analyze the differences between al-Farabi and Ibn Sina, who argue that the universe is temporally eternal through the theory of emanation (al-fayḍ), and the Islamic theological view which affirms that the world was created out of nothing (ḥudūṡ al-‘ālam). This study employs a qualitative method with a library research approach, using descriptive-analytical and comparative-critical analysis. The primary source is Tahafut al-Falasifah, supported by relevant secondary literature. The findings indicate that the philosophers conceive the relationship between God and the world as a necessary and eternal causal relation, implying that the universe has no temporal beginning, although it remains ontologically dependent upon God. In contrast, al-Ghazali rejects this necessity and asserts that God is a voluntary agent (fā‘il mukhtār) who creates the world through His free will. This debate has had a significant impact on the development of Islamic theology and philosophy, particularly in defining the respective roles of reason and revelation in addressing metaphysical questions.